Dampak Pandemi Terhadap Perekonomian Masyarakat Pedagang Batik Di Wilayah Sapuro - Rahma Sabrina (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
Covid-19 is a disease caused by the corona virus and has become a deadly pandemic outbreak throughout the world. The government has implemented a lockdown policy to suppress the growth rate of the spread of the COVID-19 virus. Various sectors of countries in the world have been affected by the pandemic, especially the economic sector. The existence of policies from the government causes various problems that occur in society such as a decrease in income, a decrease in the purchasing power of consumption, and an increasing number of unemployed in Indonesia. The purpose of this study was to determine the impact of the pandemic on the economic condition of the batik merchant community in the Sapuro area. This research method uses a qualitative method with a phenomenological study approach, this research was conducted by direct interviews in Sapuro Village, Pekalongan City with a sample of 5 respondents consisting of upper and lower middle class batik traders. From the results of interviews conducted by researchers, the results showed that the impact of the pandemic on the economic conditions of the Sapuro community, the majority of which worked as batik traders, namely there was a decrease in people's income, many people lost their jobs, increased unemployment, and decreased purchasing power for public consumption. The government seeks to overcome this problem by providing some assistance to the community such as pre-employment cards, social assistance, BLT, and quota subsidies. During the pandemic, many people depend on the assistance provided by the government to meet the needs of their families, but unfortunately the assistance provided by the government to the community is uneven because there are still a number of people who have not received this assistance. In the distribution of aid, the government should use accurate data, be selective in its selection, and increase the amount of aid capacity so that people in need will be evenly distributed in getting their assistance.Covid-19 is a disease caused by the corona virus and has become a deadly pandemic outbreak throughout the world. The government has implemented a lockdown policy to suppress the growth rate of the spread of the COVID-19 virus. Various sectors of countries in the world have been affected by the pandemic, especially the economic sector. The existence of policies from the government causes various problems that occur in society such as a decrease in income, a decrease in the purchasing power of consumption, and an increasing number of unemployed in Indonesia. The purpose of this study was to determine the impact of the pandemic on the economic condition of the batik merchant community in the Sapuro area. This research method uses a qualitative method with a phenomenological study approach, this research was conducted by direct interviews in Sapuro Village, Pekalongan City with a sample of 5 respondents consisting of upper and lower middle class batik traders. From the results of interviews conducted by researchers, the results showed that the impact of the pandemic on the economic conditions of the Sapuro community, the majority of which worked as batik traders, namely there was a decrease in people's income, many people lost their jobs, increased unemployment, and decreased purchasing power for public consumption. The government seeks to overcome this problem by providing some assistance to the community such as pre-employment cards, social assistance, BLT, and quota subsidies. During the pandemic, many people depend on the assistance provided by the government to meet the needs of their families, but unfortunately the assistance provided by the government to the community is uneven because there are still a number of people who have not received this assistance. In the distribution of aid, the government should use accurate data, be selective in its selection, and increase the amount of aid capacity so that people in need will be evenly distributed in getting their assistance.